Pertanggungjawaban Pidana Rumah Sakit Akibat Kelalaian Pelayanan Tenaga Medis dan Tenaga Kesehatan di Rumah Sakit - Wati, Indah; Sudarto, Sudarto (LITERATUS, 2025)
This thesis discusses the liability to patients for negligence committed by medical personnel, Hospitals as one form that can be constructed as a legal entity (corporation) can be categorized as legal subjects that can take legal action so that they can be accounted for. with the problem How is the Hospital's Liability if there is negligence towards patients? And What are the legal consequences for medical personnel and health workers who commit negligence towards patients?. The type of research used in this study is normative research with a descriptive analysis nature. To obtain secondary data, a literature study was carried out. Data were analyzed qualitatively and conclusions were drawn deductively. The conclusion of this study is that in order for health services to run optimally, medical personnel must always act professionally and carefully in carrying out their duties. Hospitals also need to maintain a balance between protecting the rights of patients and health workers by implementing the principle of corporate responsibility and maximizing the supervisory function. This is important to maintain the quality of health services and reduce the risk of negligence that can harm patients.